2000
DOI: 10.1097/00001756-200009110-00033
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in rat locus coeruleus in hypoxia-induced hyperventilation and hypothermia

Abstract: The locus coeruleus modulates the ventilatory and thermoregulatory response to hypoxia and contains nitric oxide synthase. Therefore, we examined the effects of L-NAME unilaterally microinjected into the locus coeruleus on hypoxic hyperventilation and hypothermia. Ventilation and body temperature were measured before and after microinjection of L-NAME (100 nmol/0.5 microl) into the locus coeruleus, followed by hypoxia. Control rats received microinjection of D-NAME (an inactive enantiomer of L-NAME). Under nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Present results show labeled cells within the locus coeruleus, with a similar morphology to that described with dopamine bhydroxylase immunohistochemistry (Hornby and Piekut, 1990). Nitrergic neurons have not previously been reported within the locus coeruleus in teleosts (Arevalo et al, 1995;Brüning et al, 1995), but they have been found in land vertebrates (Smeets et al, 1997;Fabris et al, 2000;Guo and Longhurst, 2003;Karolewicz et al, 2004;Kodama and Koyama, 2006). Consistent with previous studies in teleosts (Arevalo et al, 1995) and land vertebrates (Munoz et al, 1996;Smeets et al, 1997;Lopez et al, 2005), positive cells were also found within the different subdivisions of the raphe nucleus.…”
Section: Rhombencephalonsupporting
confidence: 92%
“…Present results show labeled cells within the locus coeruleus, with a similar morphology to that described with dopamine bhydroxylase immunohistochemistry (Hornby and Piekut, 1990). Nitrergic neurons have not previously been reported within the locus coeruleus in teleosts (Arevalo et al, 1995;Brüning et al, 1995), but they have been found in land vertebrates (Smeets et al, 1997;Fabris et al, 2000;Guo and Longhurst, 2003;Karolewicz et al, 2004;Kodama and Koyama, 2006). Consistent with previous studies in teleosts (Arevalo et al, 1995) and land vertebrates (Munoz et al, 1996;Smeets et al, 1997;Lopez et al, 2005), positive cells were also found within the different subdivisions of the raphe nucleus.…”
Section: Rhombencephalonsupporting
confidence: 92%
“…In our study, l-NAME and SIN-1 were infused i.c.v. However, as the later two regions are inhibitory nuclei (Fabris et al 2000, Gargaglioni et al 2003, NO effectively attenuates the inhibitory influence of these two nuclei during hypoxia, thereby enhancing the HVR (Fabris et al 2000, Nucci et al 2004. Within the regions of the brainstem associated with ventilatory control, NO can mediate both inhibitory and excitatory components of the HVR (Nucci et al 2004).…”
Section: Figurementioning
confidence: 99%
“…The enzyme NOS has been localized within the nucleus tractus solitarius (NTS) (Ohta et al 1993, Haxhiu et al 1995, the rostral ventrolateral medulla (Shapoval et al 1991, Kishi et al 2002 the nucleus raphe magnus (Leger et al 1998) and implicated within the locus coeruleus (Fabris et al 2000), and acute inhibition of NOS within these regions attenuates the HVR (Haxhiu et al 1995, de Paula & Branco 2003, Nucci et al 2004. The enzyme NOS has been localized within the nucleus tractus solitarius (NTS) (Ohta et al 1993, Haxhiu et al 1995, the rostral ventrolateral medulla (Shapoval et al 1991, Kishi et al 2002 the nucleus raphe magnus (Leger et al 1998) and implicated within the locus coeruleus (Fabris et al 2000), and acute inhibition of NOS within these regions attenuates the HVR (Haxhiu et al 1995, de Paula & Branco 2003, Nucci et al 2004.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia reflexively increases pulmonary ventilation by activating peripheral chemoreceptors, particularly in the carotid bodies (CB) (Taylor et al, 1999). Recent studies using in vitro models have demonstrated that endogenous gaseous compounds, such as CO, play an important role in modulating this hypoxia-induced excitation of chemoreceptors (Fabris et al, 1999(Fabris et al, , 2000Prabhakar, 1995Prabhakar, , 1999Prabhakar, , 2000Prabhakar et al, 1995;Yang et al, 1998). Several lines of evidence have suggested that CO is synthesized endogenously mainly via the catalysis of heme by heme oxygenase (HO) and functions as a chemical messenger (Maines, 1997;Prabhakar et al, 1995).…”
Section: Introductionmentioning
confidence: 99%